Loan supply shocks, prudential regulation, and the business cycle - Paul Rudel (Philipps-University Marburg, School of Business and Economics, 2024)
How do the business cycle effects of loan supply shocks depend on the state of prudential regulation in the euro area? To address this question, we first identify regulatory cycles from a cumulative prudential policy index that tracks the evolution of the regulatory stance in the euro area. Using sign restrictions in a local projections framework with state-dependency, we identify loan supply shocks and analyse their business cycle effects in regimes with tight and loose prudential regulation. We find that in tight regimes, expansionary shocks trigger a boom-bust cycle. In the loose regime, results appear inconclusive. We also see quite some tendencies toward asymmetry in the responses across regimes. To some extent, however, the results depend strongly on the cycle identified. While our results for the tight regime are very robust across different specifications, the effect of shocks on the business cycle is sensitive to identified loose regimes. The main reason is the historical development of prudential regulation in the euro area, which is primarily characterized by prudential tightening.
Keywords: C54; E32; E50; G28; 330; Prudential Regulation; Business Cycle; Loan Supply; Euro Area; State Dependence; Local Projections; Sign Restrictions